دراسة أثر كل من حجم الشركات المساهمة المسجلة في هيئة الأوراق والأسواق المالية السورية وهيكل رأسمالها على مستوى تهربها الضريبي - زيود لطيف; عيسى ريم; ريا فاتن (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى تقصي أثر كل من حجم الشركات السورية المساهمة وهيكل رأسمالها (الديون) على مستوى تهربها الضريبي. منطلقاً في ذلك من دراسات سابقة أشارت إلى احتمال وجود علاقة ما بين خصائص الشركات ومعدل الضرائب الفعال الخاص بها، وبالتالي بينها وبين مستوى تهربها الضريبي. ولتحقيق هذا الهدف تم إجراء مسح على الشركات السورية المساهمة المسجلة في هيئة الأوراق والأسواق المالية السورية، باستخدام البيانات الثانوية، وفي إطار دراسة اتجاهية تمتد من عام 2009 إلى 2014. أظهرت نتائج البحث عدم وجود علاقة ما بين حجم الشركات السورية المساهمة ومستوى تهربها الضريبي، إلا أنها خلصت إلى أن انخفاض حجم الديون في هيكل رأسمال الشركات (ممثلاً بالرافعة المالية) يترافق مع انخفاض في مستوى معدل الضرائب النقدي الفعال، وبالتالي ارتفاع في مستوى التهرب الضريبي. This research aims to investigate the impact of both the size of Syrian corporations and its capital structure on its level of tax avoidance. This study starts from number of previous studies which have indicated the possibility of a relationship between corporations characteristics and its effective tax rate, and thus between them and the level of tax avoidance. In order To achieve this goal, a survey study has been conducted on the Syrian registered corporations in the Syrian commission on financial markets and securities using secondary data with quasi-experimental design for the period from 2009 to 2014. The results of this research showed that there is no relation between the size of Syrian corporations and its level of tax Avoidance. However, it concluded that the decline in the debt volume of the corporate capital structure (represented by the leverage) is associated with a decrease in the level of effective cash tax rate and thus an increase in the level of tax avoidance.